The dynamics of climate agreements - Bård Harstad (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2009)
I study dynamic private provision of public goods (or bads) when agents (or countries) can invest in cost-reducing technologies and sign incomplete contracts. The model leads to a dynamic common pool problem that is more severe than its static counter-part. Nevertheless, a sequence of short-term agreements on contribution levels makes everyone worse oþ since countries invest less when they anticipate future negotiations. Long-term agreements induce countries to invest more. The best agreement is more demanding if the time horizon of the agreement is short and the externality from investing large (e.g., if the patent system is weak). If investments can be subsidized, the subsidy should be larger if the agreement is short-lasting. The .rst best can always be implemented by long-term agreements with renegotiations. The results have implications for the optimal design of climate treaties and they hold whether permits are tradable, non-tradable or if instead emission taxes are used.
Keywords: 330; Dynamic private provision of public goods; dynamic common pool problems; dynamic hold-up problems; time horizon of agreements; renegotiation design; climate change and climate agreements; Umweltabkommen; Klimaschutz; Unvollständiger Vertrag; Dynamisches Modell; Öffentliches Gut; Theorie